Pilgrim bell : poems - Akbar, Kaveh (Graywolf Press, 2021)
Kaveh Akbar's exquisite, highly anticipated follow-up to Calling a Wolf a Wolf... With formal virtuosity and ruthless precision, Kaveh Akbar's second collection takes its readers on a spiritual journey of disavowal, fiercely attendant to the presence of divinity where artifacts of self and belonging have been shed. How does one recover from addiction without destroying the self-as-addict? And if living justly in a nation that would see them erased is, too, a kind of self-destruction, what does one do with the body's question, "what now shall I repair? " Here, Akbar responds with prayer as an act of devotion to dissonance-the infinite void of a loved one's absence, the indulgence of austerity, making a life as a Muslim in an Islamophobic nation-teasing the sacred out of silence and stillness.... Richly crafted and generous, Pilgrim Bell's linguistic rigor is tuned to the register of this moment and any moment. As the swinging soul crashes into its limits, against the atrocities of the American empire, and through a profoundly human capacity for cruelty and grace, these brilliant poems dare to exist in the empty space where song lives-resonant, revelatory, and holy.